Meta-Analysis of Drug Delivery Approaches for Treating Intracellular Infections - Shin, Sooyoung; Kwon, Soonbum; Yeo, Yoon (Pharmaceutical Research, 2022)
This meta-analysis aims to evaluate the trend, methodological quality and completeness of studies on intracellular delivery of antimicrobial agents. PubMed, Embase, and reference lists of related reviews were searched to identify original articles that evaluated carrier-mediated intracellular delivery and pharmacodynamics (PD) of antimicrobial therapeutics against intracellular pathogens in vitro and/or in vivo. A total of 99 studies were included in the analysis. The most commonly targeted intracellular pathogens were bacteria (62.6%), followed by viruses (16.2%) and parasites (15.2%). Twenty-one out of 99 (21.2%) studies performed neither microscopic imaging nor flow cytometric analysis to verify that the carrier particles are present in the infected cells. Only 31.3% of studies provided comparative inhibitory concentrations against a free drug control. Approximately 8% of studies, albeit claimed for intracellular delivery of antimicrobial therapeutics, did not provide any experimental data such as microscopic imaging, flow cytometry, and in vitro PD. Future research on intracellular delivery of antimicrobial agents needs to improve the methodological quality and completeness of supporting data in order to facilitate clinical translation of intracellular delivery platforms for antimicrobial therapeutics.
Keywords: Anti-Bacterial Agents; Drug Delivery Systems; Antimicrobials; Drug carriers; Intracellular drug delivery; Intracellular pathogens